Lentiviral vector promoter is decisive for aberrant transcript formation - Scholz, Simone; Fronza, Raffaele; Bartholomä, Cynthia C.; Kalle, Christof von; Gil-Fariña, Irene; Schmidt, Manfred (Human gene therapy, 2017)
Lentiviral vectors hold great promise for the genetic correction of various inherited diseases. However, lentiviral vector biology is still not completely understood and warrants the precise decoding of molecular mechanisms underlying integration and post-translational modification. This study investigated a series of self-inactivating (SIN) and full long terminal repeat (LTR) lentiviral vectors that contained different types of promoters with or without a transgene to gain deeper insights in lentiviral target site selection and potential perturbation of cellular gene expression. Using an optimized nonrestrictive linear amplification-mediated polymerase chain reaction (nrLAM-PCR) protocol, vector structure-dependent integration site profiles were observed upon transduction of mouse lin- hematopoietic progenitors in vitro. Initial target site selection mainly depended on the presence of the promoter while being independent of its nature. Despite the increased propensity for read-through transcription of SIN lentiviral vectors, the incidence of viral-cellular fusion transcript formation involving the canonical viral splice donor or cryptic splice sites was reduced in both unselected primary lin- cells and transformed 32D cells. Moreover, the strength of the internal promoter in vectors with SIN LTRs is decisive for in vitro selection and for the abundance of chimeric transcripts, which are decreased by moderately active promoters. These results will help to better understand vector biology and to optimize therapeutic vectors for future gene therapy applications.